Introduction to nanocomposites - Abu, Tariq; Showkat, Ahmad Bhawani; Mohd Razip, Asaruddin; Khalid M, Alotaibi (Woodhead Publishing, 2021)
The world is changing rapidly and consistently with the emergence of new horizons in the area of science, engineering, and technology. Nanotechnology and nanocomposites form a part of nanoscience that has become a core area of attraction for scientific and technical activities. The interest in nanostructures and their usage in fields such as bio-sensors, solar cells, electronic devices, biomedical, and engineering has increased enormously over the last few years. This is because of the peculiar properties of nanostructures and their excellent efficiency in nanoscale devices. This chapter provides a detailed description of nanocomposites, their origin, classification, properties, advantages, and potential benefits highlighting the need of these peculiar and advanced materials. In addition to this, their preparation techniques and some recent findings on structure, characteristics and possible applications, and future perspectives including need of such materials in space missions and other interesting applications are also included.